Plant roots : - Gregory, Peter J. (Blackwell Pub., 2006)
The book expesses recent developments in techniques and an improved understanding of plant and soil interactions to present a comprehensive look at this important relationship. The book's content covers root response to and modification of soils; genetic control of roots responses to the environment; use of modern techniques in imaging, molecular biology and analytical chemistry; practical exploration of root characters